PENGARUH PEMBERIAN BAHAN TAMBAH KATALIS BEKAS (SPENT CATALYST) DAN FILLER SLAGTERHADAP CAMPURAN BETON SEMEN UNTUK PERKERASAN JALAN - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
Local/waste materials have commonly been used, however, they are now being evaluated and need further research to find out that they are really suitable for cement mixing. In Indonesia there are local and waste materials that can be either directly used in cement mixing such as slag, fly ash or processed in order to be used in cement mixing like spent catalyst. The purpose of the research is to utili se waste material, spent catalyst as a mineral admixture in cement mixing and to improve its perfomance, since the catalyst has a Pozzolan characteristic. Residium Catalityc Cracking (RCC) or spent catalyst is a waste material from oil refinery in Balongan , Indramayu.,West Java. Another material used in cement mixing is slag, as a local material or by product from steel manufacture PT Krakatau Steel in Cilegon,Province of Banten. Experiments were done by adding 10% spent catalyst and 10% filler slag to the standard cement mixing, after 28 days the result has not complied to the specification for road pavement, it had compressive strength less than 30 Mpa. (Section 5.1. General Specification for Road and Bridge,2005) The density after curing 28 days, cement mixing used 10% of spent catalyst and 10% of filler slag , had density more than 2,200 kg/dm3 ( the specification between 2,200 kg/dm3 to 2,500 kg/dm3) The addition of 20% spent catalyst and 20% of filler slag, has compressive strength increased more than 30 Mpa after curing 28 days. However, by adding 1,5% superplastizier to the mixed the compressive strength decreased less than 30 MPa. Research is continued by extending curing period up to 56 days, compressive strength of all mixes increased sharply between 40 MPa to 50 MPa. It was concluded that filler slag can be used as an additive in cement mixing, since it has a compressive sterength higher than the standard cement mixing. Keywords: Spent catalyst, filler slag, Cement mixing, compressive strength, density